Foreign-Currency Positioning by U.S. Firms: Some New Evidence - Fieleke, Norman S. (The Review of Economics and Statistics, 1981)
S ince the breakdown of the par-value system there has been a dramatic increase in the variability of exchange rates. Often the question is raised whether this variation is rational or whether it is the outcome of disorderly markets which are bereft of stabilizing speculation or-even worse-are dominated by destabilizing speculation. The considerable research stimulated by this issue has yet to yield conclusive results, and whether the foreign-exchange market is rational or efficient is still an open question.' Of course, the market is not an abstraction but is comprised of flesh-and-blood participants whose behavior may show varying degrees of rationality. This paper utilizes a new body of data to undertake a preliminary investigation into the market behavior of one major group of participants: U.S. firms whose foreign-currency positions are regularly reported to the U.S. Government.